Maximizing the value of values-based leadership (VBL): A reconceptualization for leaders and organizations - Mark D. Fulford; Robert A. Coleman (Journal of Applied Leadership and Management, 2021)
Research Questions: Over the last two - three decades or so, a plethora of research has been conducted on values-based leadership (VBL) and related leadership constructs. However, has any real progress been made? Could a change in focus contribute more value to the practical and theoretical implications of VBL? Methods: The Research Questions are addressed via a reconceptualization of VBL itself, along with an expansion of its scope to include follower, leader, and organizational components. Results: A broader operational definition of the VBL construct is proposed; it is argued that assumptions regarding the existence of a universal desired set of values (including ethics) do not belong; and follower perceptions of leader effectiveness should take precedence over reliance on leader self-reports. Focus should be redirected on several aspects of fit: that between the stated and lived values of the leader; between the values of the leaders and their followers; and between the leaders and the organization.
Keywords: 650